Efectos de detergentes biodegradables en la acumulación de lipofuscina (pigmento de envejecimiento) en branquias e hígado de dos espécies de peces neotropicales - Pereira, Bruno Fiorelini; Alves, Anderson Luis; Senhorini, José Algusto; Rocha, Rita de Cássia Gimenes de Alcântara; Pitol, Dimítrius Leonardo; Caetano, Flávio Henrique [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2014)
Currently there is a growing concern, in both population and governments, to identify the effects of substances commonly disposed of into rivers and lakes, on aquatic fauna and flora. Thus the objective of the present study was to verify effects of biodegradable detergents and water from an urban lake on gills and liver of two neotropical fish species of great economic importance, Astyanax altiparanae and Prochilodus lineatus. In order to do so, lipofuscin, also called the ageing pigment, was used as bioindicator. After one and five months of experiment both tissues accumulated this pigment. These data are discussed from physiological points of view, related with lipid peroxidation and mitochondrial damage.
Effects of biodegradable detergents in the accumulation of lipofuscin (age pigment) in gill and liver of two neotropical fish species
Keywords: Astyanax; Gill; Lipofuscin; Liver; Prochilodus